1986
DOI: 10.1037/0022-3514.51.3.578
|View full text |Cite
|
Sign up to set email alerts
|

Role quality, multiple role involvement, and psychological well-being in midlife women.

Abstract: Women's occupancy of the social roles of paid worker, wife, and mother, and the quality of their experience in these three roles, were examined in relation to psychological well-being. Data were from a disproportionate random sample (N -238) of Caucasian women ages 35 to 55. Well-being was measured by indices of self-esteem, depression, and pleasure; pleasure was assessed by a scale consisting of single-item measures of happiness, satisfaction, and optimism. Role quality was measured by scales developed for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
270
4
15

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 412 publications
(306 citation statements)
references
References 35 publications
17
270
4
15
Order By: Relevance
“…Family-related variables were measured by number of children at home and spouse support. Spouse support was measured by eight items from a factor analysis of the modified scale of Baruch and Barnett's (1986) spousal experience. Sample items include 'Good communication' and 'Husband backing you up'.…”
Section: Methodsmentioning
confidence: 99%
“…Family-related variables were measured by number of children at home and spouse support. Spouse support was measured by eight items from a factor analysis of the modified scale of Baruch and Barnett's (1986) spousal experience. Sample items include 'Good communication' and 'Husband backing you up'.…”
Section: Methodsmentioning
confidence: 99%
“…Other research has found no significant difference in the mental health outcomes between employed and unemployed women. [7,[11][12][13][14][15][16] Repetti et al compared the distress levels of employed and unemployed single and married women, and found that employment was associated with improved mental health for both groups. [17] A more recent study, which used a large, national sample, found that mental well-being was positively related to the mother's employment and negatively related to her total number of children.…”
Section: Employmentmentioning
confidence: 99%
“…[7] More recent research indicates that involvement in each role has both harmful and beneficial effects, and the balance between these varies depending on the characteristics of the role, the specific combination of roles, and the socio-economic context of women's lives. [8] Socio-economic status creates different experiences and exposures in daily life and these, in turn, have consequences for women's psychological health.…”
mentioning
confidence: 99%
“…The family related variables most often addressed as antecedents of conflict in these studies include: parental status, or the number and ages of children (Beutell and Greenhaus, 1982;Cartwright, 1978;Greenhaus and Kopelman, 1981;Keith and Schafer, 1980;Kingston and Nock, 1985;Pleck et al, 1980;Shamir, 1983); employment status of the spouse (Greenhaus and Kopelman, 1981;Pleck and Staines, 1982;Pleck et al, 1980; ) and the number of roles a woman occupies (Barnett, 1982;Baruch and Barnett, 1986;Cooke and Rousseau, 1984;Hall, 1975;Herman and Gyllstrom, 1977;Holahan and Gilbert, 1979b). Studies focusing on the number or types of roles occupied typically look for differences in the experience of work/family conflict as a function of being single, married with no children, or married with children.…”
Section: Work/family Conflict Literaturementioning
confidence: 99%
“…The majority of work/family conflict studies are based on a role theory perspective of interrole conflict (Barnett, 1982;Baruch and Barnett, 1986;Greenhaus, 1982, 1983;Frone and Rice, 1987;Gilbert and Holahan, 1982;Greenhaus and Beutell, 1985;Greenhaus and Kopelman, 1981;Hall, 1972Hall, , 1975Hall and Gordon, 1973;Herman and Gyllstrom, 1977;Gilbert, 1979a, 1979b;Kopelman, Greenhaus and Connolly, 1983;Shamir, 1983). According to role theory (Kahn, Wolfe, Quinn, Snoek, and Rosenthal, 1964), individuals simultaneously occupy a number of different roles in their lives.…”
Section: Work/family Conflict Literaturementioning
confidence: 99%